Guarany memory and history revealed through civic engagement in the triple border (Argentina, Brazil And Paraguay) - Brighenti, Clovis Antonio (Guará Journal, 2018)
This article summarizes the extension project: “Indigenous memory and pedagogical reparations in the border region”, developed at the Universidade Federal da Integração Latino-Americana in 2016. As professors, we aim to register the indigenous memory through the relationship with the Guarani population in the state of Paraná in Southern Brazil, especially in dialogue with their leaders. We examine the actions by the Brazilian State as a violator of rights of the Guarani people in the second half of the twentieth century. At that time, indigenous population lost their land in three distinct processes: the colonization of western Paraná; the creation of the Iguaçu National Park; and the construction of the Itaipu Binacional Hydroelectric Power Plant. We will use as a reference the pedagogical education recommendations of the Final Report published by the National Truth Commission (CNV) on December 2014, which was sent to the Brazilian State.